Vascular Effects of Achieving Low Disease Activity in Axial Spondyloarthritis - A 2-Year Prospective Cohort Study - Huan Meng; Xerox SL Lau; Isaac TH Cheng; Byran P Yan; Alex P Lee; Ho So; LS Tam (Journal of Clinical Rheumatology and Immunology)
Background: Axial spondyloarthritis (axSpA) is associated with accelerated atherosclerosis driven by chronic inflammation. Achieving LDA may result in significant benefits in articular disease, little is known about its effect on extra-articular disease, including CVD risk in axSpA. To investigate the effect of achieving Ankylosing Spondylitis Disease Activity Score (ASDAS) low disease activity (LDA) using a protocolized treatment strategy on the progression of subclinical atherosclerosis and arterial stiffness in axial spondyloarthritis (axSpA) patients. Methods: One hundred consecutive AxSpA patients will participate in this 2-year prospective, hospital-based, cohort study. All participants will receive 2 years of tight-control treatment. Treatment will be adjusted according to a standardized protocol every 3-6 monthly aiming at ASDAS LDA (ASDAS <2.1). Carotid intima-media thickness (IMT) and total plaque area (TPA) will be measured using high-resolution ultrasound. Arterial stiffness is measured by pulse wave velocity (PWV) and augmentation index (AIx). The main outcome measure is the change in subclinical atherosclerosis over a period of 2 years comparing between patients who achieve sustained LDA at year 2 (sLDA group: achieved LDA at both year 1 and year 2) to those who cannot achieve LDA (non-sLDA group). Secondary outcomes include differences in the changes in AIx and PWV over 2 years between the 2 groups. Results: In this interim analysis, a total of 56 axSpA patients (age: 38± 10 years, 43 (76.8%) male) who completed 2 year of follow-up were included. A significant improvement in disease activity was observed after 2 years of treatment (ASDAS-CRP at baseline: 2.9± 0.6 vs 1.9± 0.7 at year 2, p<0.001). Forty-one patients achieved LDA at year 1 and 31 patients achieved sustained LDA (sLDA) at year 2. The baseline traditional CV risk factors were comparable between the sLDA and non-sLDA groups. The multivariate analysis demonstrated that the sLDA group exhibited a smaller increase in mean IMT ([Formula: see text]: -0.04, 95%CI -0.07 to -0.01, P=0.025) and max IMT ([Formula: see text]: -0.06, 95%CI -0.12 to -0.004, P=0.038) after adjustment for covariates compared to the non-sLDA group. However, there were no significant differences in the progression of carotid plaque and arterial stiffness markers between the two groups in the multivariate analysis. Conclusion: Patients with AxSpA who are able to achieve sLDA through a protocolized treatment algorithm experience reduced progression of subclinical atherosclerosis compared to patients who cannot achieve sLDA. This indicates that effective suppression of inflammation in AxSpA patients who reach sLDA may potentially lower CV risk.